NH3 Partnership working to achieve successful Health Board-Wide Hepatitis B Partner Notification Outcomes. (30th June 2016) - King, Sam; Harbut, Chris; Murchie, Martin
Abstract : Background/Introduction: The Sandyford Shared Care Support and failsafe (SSCS) service managed by the Sexual Health Advisers provides advice and support to NHS Greater Glasgow and Clyde Health Care Professionals in the management of individuals diagnosed with a sexually transmitted infection or blood borne virus. In relation to Hepatitis B infection their role is to make contact with testing clinicians by telephone to review the case, facilitate timely results giving and onward referral to appropriate specialist services, co-ordinate and assist with public health activities arising from each case, document and audit outcomes. Aims(s)/Objectives: To demonstrate the impact of SSCS support to promote partnership working to achieve effective and auditable partner notification outcomes for acute and chronic Hepatitis B cases. Methods: Acute or chronic Hepatitis B cases between 1 September 2012 and 31 December 2015 were reviewed. Partner notification outcomes documented for identified sexual partners, family and household contacts requiring testing and vaccination were examined. Results: A total of 710 cases of Hepatitis B were reported to SSCS during the audit period (675 chronic and 35 acute). 1278 contacts were identified, and 840 contacts (1.18 per index case) were reported (verified or unverified) to have attended a service for assessment. 656 contacts were vaccinated, 113 had immunity and 62 found to have active infection. Discussion/Conclusion: This audit clearly demonstrates the value and importance of partnership working to achieve successful public health outcomes well above targets set by national standards.